Benefits of once-daily dosing with non-vitamin K antagonist oral anticoagulants in patients with atrial fibrillation. (21st April 2016) - Amara, Walid; Antoniou, Sotiris
Abstract: Atrial fibrillation (AF) is the most prevalent clinically relevant arrhythmia, affecting millions of individuals in Europe and the USA. Atrial fibrillation increases the risk of stroke; the long-term standard of care for prevention of AF-related stroke is anticoagulation. The use of anticoagulants should be based on the absolute risks of stroke and bleeding and the relative benefit–risk profile of the individual patient. Treatment options include vitamin K antagonists (VKAs) such as warfarin, whose use is long-established but associated with drawbacks, including regular coagulation monitoring requirements and many food and drug interactions. The non-VKA oral anticoagulants are gaining widespread use as alternatives to VKAs, and are supported in treatment guidelines for patients with AF at moderate to high risk of stroke. Adherence to medication is important for the long-term efficacy of any therapy; however, relatively low levels of medication adherence are to be expected in 'real-world' AF patients compared with clinical trials. Experience across several therapy areas, including cardiovascular disease, shows that poor adherence to chronic medication is common. However, simple dosing schedules may be advantageous in this respect, and because long-term outcomes in AF are likely to be influenced by adherence, once-daily dosing has the potential to improve rates of stroke prevention in patients with AF.